2013
DOI: 10.2139/ssrn.2340824
|View full text |Cite
|
Sign up to set email alerts
|

Just Interested or Getting Involved? An Analysis of Superannuation Attitudes and Actions

Abstract: Australians have contributions made to their super funds whether they like it or not. Members should not have to be interested, financially literate, or investment experts to get the most out of their super funds. If members want to engage and make choices, then the system ought to encourage and facilitate them doing so. If members are not interested, then the system should still work to provide optimal outcomes for them. The super system should work for its members, not vice versa. This is the basis of the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 16 publications
(8 reference statements)
5
16
0
Order By: Relevance
“…Our empirical results are consistent with these findings. Some international evidence, however, also supports the notion that a large number of choice options causes confusion, which leads to high rates of default Tapia and Yermo, 2007;Vanguard, 2008;Benartzi et al, 2011;Bateman et al, 2014). Our simulations confirm this theory in the context of the Australian higher education sector and quantify the large impact of default provisions on savings.…”
supporting
confidence: 75%
“…Our empirical results are consistent with these findings. Some international evidence, however, also supports the notion that a large number of choice options causes confusion, which leads to high rates of default Tapia and Yermo, 2007;Vanguard, 2008;Benartzi et al, 2011;Bateman et al, 2014). Our simulations confirm this theory in the context of the Australian higher education sector and quantify the large impact of default provisions on savings.…”
supporting
confidence: 75%
“…This will allow providers to target their marketing efforts to members of each cluster, based on these attitudes, in order to increase their engagement. We emphasize interest and trust because they are known motivators of nondefault behavior, which is our way of defining engagement (Agnew et al 2012;Bateman et al 2014;Brown and Krishna 2004;Hedesström, Svedsäter, and Gärling 2007), but we also allow for other attitudes that could reduce engagement, such as complacency or a perceived lack of need ("sufficiency" from here on; Rickwood and White 2009).…”
Section: Engagement Interest and Trustmentioning
confidence: 99%
“…We study the association between attitudes (such as interest and trust) toward retirement savings and observable levels of engagement, as evidenced through nondefault behavior (e.g., when members select a nondefault investment option, change insurance cover, make additional contributions, and interact with the pension plan provider online). Bateman et al (2014) studied how observed engagement relates to two attitudes: members' interest in retirement savings, arguably a combination of needs-based situational interest and more enduring, enjoyed individual interest (Hidi and Harackiewicz 2000), 2 and members' likelihood to recommend, or advocate for, their pension plan provider. While highly interested members are more likely to use the plan's online services or to make additional contributions, they are no more likely than less interested people to opt out of default investment or insurance settings.…”
mentioning
confidence: 99%
“…However recent studies show that this conclusion is too simplistic. First, active interest in superannuation grows with the stakes, and with capability, so that members who have more savings, steady incomes, more education or skill are more likely to opt out of default settings (Bateman et al, 2014). The implication is that as the SG system matures and members' balances rise, then so too will their interest.…”
mentioning
confidence: 99%
“…Secondly, 'interest' has been poorly measured. While the activities that best indicate member interest are monitoring (e.g., looking up information on fund websites) and voluntary contributions, most discussion has emphasised investment choice or choice of fund, that are more weakly related to interest (Bateman et al, 2014;Deetlefs et al, 2015). Thirdly, social influences that are not always considered by economists matter to activity and sometimes dominate instrumental factors (Croy et al, 2010(Croy et al, , 2012.…”
mentioning
confidence: 99%